Saccade-Related, Long-Lead Burst Neurons in the Monkey Rostral Pons - Kaneko, Chris R. S. (2005)
The paramedian pontine reticular formation contains the premotoneuronal cell groups that constitute the saccadic burst generator and control saccadic eye movements. Despite years of study and numerous investigations, the rostral portion of this area has received comparatively little attention, particularly the cell type known as long-lead burst neurons (LLBNs). Several hypotheses about the functional role of LLBNs in saccade generation have been proposed, although there is little information with which to assess them. To address this issue, I mapped and recorded LLBNs in the rostral pons to measure their discharge characteristics and correlate those characteristics with the metrics of the concurrent saccades. On the basis of their discharge and location, I identified three types of LLBNs in the rostral pons: excitatory (eLLBN), dorsal (dLLBN), and nucleus reticularis tegmenti pontis (nrtp) LLBNs. The eLLBNs, encountered throughout the pons, discharge for ipsilateral saccades in proportion to saccade amplitude, velocity, and duration. The dLLBNs, found at the pontomesencephalic junction, discharge maximally for ipsilateral saccades of a particular amplitude, usually <10°, and are not associated with a particular anatomical nucleus. The nrtp LLBNs, previously described as vector LLBNs, discharge for saccades of a particular direction and sometimes a particular amplitude. The discharge of the eLLBNs suggests they drive motor neurons. The anatomical projections of the nrtp LLBNs suggest that their involvement in saccade production is less direct. The discharge of dLLBNs is consistent with a role in providing the “trigger” signal that initiates saccades.